(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To identify skin care strategies for newborns (NB) used in reference centers of the Kangaroo-Mother Care Method (KMC) in Brazil. Methods: Descriptive exploratory study, using a qualitative approach, performed with 13 nurses working in the different reference centers of the KMC in Brazil. Data were collected through an online form. Analysis was performed descriptively, comparing the different studies realities. Results: Four categories were described regarding skin care of NB through the experience of the nurses: strategies adopted by the team regarding skin care of NBs; dealing with the health team regarding bath and dipper disposal; care regarding fixation of devices in NBs, and strategies adopted by the NB team under phototherapy. Conclusion: The nurses presented capacity, and they were highly trained to act in their areas of experience and knowledge. The answers indicated that there is a great concern in avoiding the usage of materials and devices that could cause harm to NB skin.